THE “CHILDREN IN THE STREET” IN THE GENERAL OBSERVATION 21 OF THE COMMITTEE FOR CHILDREN RIGHTS. TRANSFIGURATION A CATHEGORY OF SOCIAL COMPREHENSION (Perspectivas de las Ciencias Económicas y Jurídicas, 2020)
The first formal use of the term “street children” in the Human Rights Protection systems refers to the case “Villagrán Morales and others against Guatemala”, from the Inter-American Court of Human Rights, of 1999. The sentence was criticized by an important group of doctrinaires because the use of that expression, ultimately, contains a segregative classification of childhood. In a time of expansion of rights, the Court refloated a typical concept of the irregular situation doctrine. However, in 2017 the Committee on the Rights of the Child refloated the expression in the General Comment 21 to set up a social category useful to formulate an integral approach to human rights conception and contemplating mechanisms of prevention and answer. The approach of the Committee has the particularity of being configured by the active participation of groups of children from different regions and proposes the challenge, on a human rights perspective, to return to work with categories within the group.
Keywords: street children; human rights; rights of children; irregular situation doctrine; integral protection of rights doctrine; category of social comprehension.